An exploration of jealousy in nursing: A Kleinian analysis. Issue 2 (30th May 2013) - Evans, Alicia M; Traynor, Michael; Glass, Nel
<x xml:space="preserve">Abstract</x> It is well established that nursing practice produces considerable anxiety, and it can also give rise to envy and jealousy. While envy in nursing was identified in the literature more than 50 years ago, there remains a paucity of articles addressing either envy or jealousy for nurses. In a recent research study on current experiences of clinical practice, we analysed a fragment of nurses' speech via Klein's theory of jealousy. The results revealed that the nurses expressed jealousy at the privilege afforded to doctors. We argue that it is important to acknowledge jealousy in nursing practice because it has the potential for 'spoiling' effective care delivery and as such, can have detrimental ramifications in the health system. Also, jealousy may keep the nurse from fully focusing on their nursing practice in that it divides the nurse's attention and so limits the nurse's treatment of the patient. Nurses' jealousy of doctors is a taboo topic in nursing, and yet it warrants serious consideration due to the potential deleterious consequences that can arise when this dynamic is present.